Science, Technology, Engineering, and Mathematics Literacy Analysis of Pre-service Biology Teachers in Indonesia - R. Ahmad Zaky El Islami; Indah Juwita Sari; Jun. S Camara; Prasart Nuangchalerm (JIPI (Jurnal IPA & Pembelajaran IPA), 2025)
STEM (science, technology, engineering, and mathematics) education has had a significant positive impact on students in recent years. The urgency of this research is to identify knowledge and skills gaps so that we can formulate more relevant educational strategies to face the challenges of the technology and innovation era. This study aims to analyze the STEM literacy of pre-service biology teachers in Indonesia. The case study used in this study with the sample used were 45 volunteer pre-service biology teachers at a public university in Serang, Indonesia by the purposive sampling technique who enrolled in the department of biology education. The results obtained show that most of the pre-service biology teachers have good STEM literacy. It can be concluded that pre-service biology teachers in Indonesia demonstrate a fairly good level of STEM literacy.